Experimental rejection of a nonadaptive explanation for increased cell size in Escherichia coli. - Mongold, J A (1996)
Populations of Escherichia coli that have been serially propagated for thousands of generations in glucose minimal medium show heritable increases in both cell size and growth rate. We sought to test the hypothesis that the increased cell size of the derived genotypes could be explained solely by their faster growth. The regression of cell size on growth rate differed significantly between populations having ancestral and derived genotypes, with the latter producing larger cells over almost the entire range of growth rates. Thus, the physiological coupling between cell size and growth rate has been evolutionarily altered.